2019
DOI: 10.1080/23337931.2019.1591967
|View full text |Cite
|
Sign up to set email alerts
|

Anti-demineralization effect of desensitizer containing copolymer and sodium fluoride on root dentin – a transverse microradiographic study

Abstract: Objective: To evaluate anti-demineralization effects of dentin desensitizer containing sodium fluoride and methacrylate-co-p-styrene sulfonic acid (MS polymer) on root dentin using transverse microradiography (TMR).Material and methods: Twenty-four dentin specimens were divided into four groups: MSO (no fluoride), MSF (3000 ppm F), FJL (9000 ppm F), and Control. In MSO and MSF, each desensitizer was rubbed into the dentin surfaces for 10 s then left for 20 s. In FJL, paste containing 9000 ppm F was applied ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Poly (amidoamine) (PAMAM) and rechargeable composite incorporating nanoparticles of calcium phosphate (NACP) have also been reported to achieve dentin remineralization completely and restore the hardness similar to healthy dentin, so that PAMAM plus recharged NACP remineralized predemineralized dentin completely, with prolonged fluid challenge like to the oral environment (18) . Moreover, it was suggested that dentin desensitizer containing 3000ppm fluoride and methacrylate-cop-styrene sulfonic acid (MS polymer) has the same anti-demineralization effect on root dentin lesion as does a fluoride paste containing 9000ppm F (19) . Furthermore, it was reported that fluoride dentifrice was capable to hamper further demineralization of sound dentin as well as lowly and highly demineralized dentin artificial caries (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Poly (amidoamine) (PAMAM) and rechargeable composite incorporating nanoparticles of calcium phosphate (NACP) have also been reported to achieve dentin remineralization completely and restore the hardness similar to healthy dentin, so that PAMAM plus recharged NACP remineralized predemineralized dentin completely, with prolonged fluid challenge like to the oral environment (18) . Moreover, it was suggested that dentin desensitizer containing 3000ppm fluoride and methacrylate-cop-styrene sulfonic acid (MS polymer) has the same anti-demineralization effect on root dentin lesion as does a fluoride paste containing 9000ppm F (19) . Furthermore, it was reported that fluoride dentifrice was capable to hamper further demineralization of sound dentin as well as lowly and highly demineralized dentin artificial caries (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Dentin specimens were prepared as described 15,17,18) . The experimental procedures are outlined in Fig.…”
Section: Preparation Of Experimental Specimensmentioning
confidence: 99%
“…A scan of each section was performed at the center of the lesion, and values were calculated for three parameters: mineral content profile, integrated mineral loss (IML: vol%×µm), and lesion depth (LD: µm). The values of two sections from each specimen were averaged 4,29,30) .…”
Section: Tmr Analysismentioning
confidence: 99%
“…While such demineralization includes both bacterial and nonbacterial agents, desensitizers with remineralization ability would be useful. Although anti-demineralization effects of desensitizers have been studied [3][4][5] , no study has reported the remineralizing effects of desensitizers using transverse microradiography (TMR) in predemineralized root dentin. TMR, which reveals precise levels of mineral loss, is widely recognized as the gold standard method in demineralization and remineralization studies of both enamel and dentin [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%